2004
DOI: 10.1002/uog.1013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of umbilical artery intermittent absent and/or reversed end‐diastolic flow in complicated and uncomplicated monochorionic twin pregnancies

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
3
22

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 12 publications
6
97
3
22
Order By: Relevance
“…The reports by Gratacos et al 4,5,13 showed that sIUGR is associated with intermittent UA flow pattern (type III) and that the type of Doppler alteration is related to the number and diameter of artery-artery anastomoses. That prompted us to investigate if there were any differences between the sIUGR and nsIUGR groups regarding Doppler flow pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports by Gratacos et al 4,5,13 showed that sIUGR is associated with intermittent UA flow pattern (type III) and that the type of Doppler alteration is related to the number and diameter of artery-artery anastomoses. That prompted us to investigate if there were any differences between the sIUGR and nsIUGR groups regarding Doppler flow pattern.…”
Section: Discussionmentioning
confidence: 99%
“…A greater incidence of marginal or velamentous umbilical cord insertion, unequal sharing of the placental bed, and unbalanced arterio-venous anastomoses, with consequent compensatory mechanisms, make each monochorionic placenta an individual and atypical arrangement. 2,3 Gratacos et al, 4 in 2004, initiated a series of studies demonstrating increased neonatal morbidity in monochorionic and diamniotic (MCDA) pregnancies affected by sIUGR with abnormalities in Doppler velocimetry. In 2007, Gratacos et al, 5 comparing groups of sIUGR-affected MCDA pregnancies with different umbilical artery Doppler velocimetry patterns (normal Doppler, persistent absent or reversed end diastolic velocity flow, intermittent absent or reversed end diastolic velocity flow), reported, in the group with the latter pattern, a higher rate of intrauterine death (IUD) in the smaller fetus and of brain lesions in the larger fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Селективная задержка внутриутробного роста плода (СЗВРП) встречается примерно в 9,9% наблюдений моно-хориальных близнецов [14,17,18].…”
Section: таблица 1 исходы малоинвазивной лазерной коагуляции сосудовunclassified
“…R. Quintero и соавт. [14,18] позиционировали данный тип лечения как альтерна-тивный подход к лечению при СЗВРП у монохориальных двоен [4,14].…”
Section: таблица 1 исходы малоинвазивной лазерной коагуляции сосудовunclassified
See 1 more Smart Citation